The Influence of Financial Technology on the Financial Performance of MSMEs in Malang - Erna Retno Rahadjeng; Sudarmiatin Sudarmiatin; Agus Hermawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of using financial technology (Peer To Peer Landing, Risk and Investment Management, Market Aggregator and Payment Gateway) on the financial performance of SMEs in the city of Malang. This research is a quantitative research with the research population is the perpetrators of SMEs in the city of Malang. The analytical model used in this research is descriptive analysis, classical assumption test and multiple regression. The results showed that Peer To Peer Landing, Risk and Investment Management, Market Aggregator and Payment Gateway had an effect on the financial performance of MSMEs in Malang City. The results of the research are expected to be able to contribute to MSME actors who use fintech in carrying out their operational activities Keywords: financial technology, Peer To Peer Landing, Risk and Investment Management, Market Aggregator and Payment Gateway, financial performance.